'Fighting' McKenzie ANZAC chaplain : tribute to a hero - Stringer, Col (Robina Town Centre, QLD Col Stringer Ministries, 2002)
Includes bibliographical references.
Keywords: McKenzie, William, -- 'Fighting Mac', -- 1869-1947; Church history -- Australia -- biography